The role of protease-activated receptors (PARs) in the functioning of platelets and platelet-derived microparticles (PMPs) - Jakobsche-Policht, Urszula; Bronowicka-Szydełko, Agnieszka; Adamiec, Rajmund; Bednarska-Chabowska, Dorota; Mierzchała-Pasierb, Magdalena; Lewandowski, Łukasz; Gostomska-Pampuch, Kinga; Adamiec-Mroczek, Joanna; Rabczyński, Maciej; Kuźnik, Edwin; Lubieniecki, Paweł; Dróżdż, Olgierd; et al. (Frontiers in Molecular Biosciences, 2025)
Protease-activated receptors (PARs), present on the surface of platelets and platelet-derived microparticles (PMPs), belong to a superfamily of membrane receptors that play a key role in initiating intracellular G protein-dependent signaling pathways. Although four types of PARs have been identified–PAR-1, PAR-2, PAR-3, and PAR-4 – their mechanisms and functions remain poorly understood. Nevertheless, they are considered promising therapeutic and diagnostic targets, as they play crucial roles in initiating and promoting processes such as coagulation, inflammatory responses, and vascular function. PAR-1 is expressed on various cell types, including endothelial cells, platelets, neurons, and immune cells. Its activation by thrombin initiates a G protein-dependent signaling cascade that stimulates the expression of cytokines, selectins, adhesion molecules, and growth factors. In addition to thrombin, PAR-1 can also be activated by activated protein C (APC) and matrix metalloproteinase-1 (MMP-1). APC triggers cytoprotective signaling pathways, while MMP-1 influences cellular dynamics through alternative signaling mechanisms. PAR-1 activation is also affected by epigenetic modifications and genetic polymorphisms in the PAR-1 gene. Variants such as −1426 C/T and −506 I/D influence receptor expression and are associated with an increased risk of thrombosis, potentially due to epigenetic changes linked to atherosclerosis. The complex signaling network of PAR-1 makes it a promising therapeutic target for the treatment of cardiovascular diseases, cancer, and neuroinflammatory disorders. This paper serves as a compendium on PAR-1 and its role, particularly in the activation of platelets and PMPs.